Enhanced effect of carbon nanofibers on heating efficiency of conductive cementitious composites under ohmic heating curing. (March 2021) - Tian, Weichen; Liu, Yushi; Qi, Beimeng; Wang, Wei
Abstract: Ohmic heating (OH) curing method has been proved to cure conductive fibers enhanced cementitious composites by electric-heating conversion under ultralow temperature, and this curing effect depends greatly on the heating efficiency. This paper presents a novel idea of utilizing carbon nanofibers (CNFs) to regulate and control the heating efficiency of carbon fibers (CFs) enhanced cementitious composites. The heating efficiency including peak curing temperature and temperature-increase rate of CF/CNFs reinforced cementitious composite (CF/CNF-CCC) with 0–0.3 vol% CNFs addition are traced. Results show that the increasing addition of CNFs shows a significantly increased enhancement effect to the heating efficiency during OH curing, in which the peak curing temperature and temperature-increase rate are increased from 44.8 °C to 0.139 °C/min to 73.2 °C and 0.39 °C/min as the content of CNFs is increased from 0 to 0.3 vol%. The microstructural heating mechanism based on CNFs distribution type in CF/CNF-CCC samples is clarified, two CNFs "bridge effects" are considered to effectively construct microscopic conductive network of CNFs among macroscopic conductive network of CFs. COMSOL Multiphysics simulation is conducted to further verify the improving effect of CNFs on the heating efficiency and to quantificationally guide the material composition design of CF/CNF-CCC for achieving the controllability of heating efficiency. Highlights: Percolation and experimental analysis are performed to determine the optimal CFs content. Heating efficiency of CF-CCC is largely enhanced with increased addition amounts of CNFs. Microstructural heating mechanism is mathematically clarified by presenting CNFs distribution type. Multiphysics simulation is conducted to quantificationally describe the improving effect of CNFs on heating efficiency.